2011
DOI: 10.1002/ejoc.201100550
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II)‐Catalyzed Asymmetric Hydrosilylation of Acetophenone

Abstract: Four new ligands containing a pentasubstituted cyclopentadiene tethered to a stereogenic diamine unit have been prepared and used in the iron‐catalyzed enantioselective hydrosilylation of acetophenone. Catalytically active species have been generated in situ starting from various sources of iron. Fe(acac)2 was the catalyst precursor of choice, whereas other simple FeII or FeIII compounds resulted in significantly lower or no catalytic activity. Quantitative conversions were obtained working with 4 mol‐% Fe at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Togni has shown that an in-situ-formed catalyst from cyclopentadienyl-bearing chiral diamine (L26) and Fe(acac) 2 promoted the reduction of ketones affording the corresponding alcohols with conversion up to 99% but with low to moderate ee up to 37% (Scheme 70). 296 Pincer-type iron complexes, which are usually more stable and efficient in hydrogenation, were also extensively reported in hydrosilylation of carbonyl compounds.…”
Section: Aldehydes and Ketonesmentioning
confidence: 99%
“…Togni has shown that an in-situ-formed catalyst from cyclopentadienyl-bearing chiral diamine (L26) and Fe(acac) 2 promoted the reduction of ketones affording the corresponding alcohols with conversion up to 99% but with low to moderate ee up to 37% (Scheme 70). 296 Pincer-type iron complexes, which are usually more stable and efficient in hydrogenation, were also extensively reported in hydrosilylation of carbonyl compounds.…”
Section: Aldehydes and Ketonesmentioning
confidence: 99%
“…Coordinatively unsaturated transition metal (TM) carbonyls are known to catalyze various processes, primarily the hydrogenation, isomerization, and hydroformylation of olefins, C–H bond activation, and Fischer–Tropsch and water–gas-shift reactions. ,, Iron carbonyls are widely used in manufacturing new materials and epitaxial layers . Fe(CO) 5 is particularly used in preparation of carbon nanotubes via the catalytic chemical vapor deposition, where molecular hydrogen plays an important role in the growth and microstructure of nanotubes .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nontoxic and cheap, but achiral, iron catalysts have been mainly used in hydrogenation, hydrosilylation, and cross-coupling reactions . In contrast, only a handful of chiral catalysts have been developed for enantioselective transformations such as hydrosilylation, direct H 2 -hydrogenation (AH), and transfer hydrogenation of ketones (ATH). Despite spectacular advances, the stability of iron catalysts is still a major issue.…”
mentioning
confidence: 99%